2021
DOI: 10.3390/polym13193212
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Stable Nanocomposites Containing Copper Nanoparticles Incorporated in Poly-N-vinylimidazole

Abstract: New stable nanocomposites with copper nanoparticles (CuNPs) in a polymer matrix have been synthesized by green chemistry. Non-toxic poly-N-vinylimidazole was used as a stabilizing polymer matrix and ascorbic acid was used as a reducing agent. The polymer CuNPs nanocomposites were characterized by Fourier transform infrared (FTIR) spectroscopy, ultraviolet–visible (UV) spectroscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic absorption spectroscopy (AAS), and thermogravim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…However, the detected effect can be attributed not only to the influence of silver ions/nanoparticles on the polymerization conditions, but also to the intermolecular crosslinking of individual PVT macromolecules by nanoparticles into aggregates. Previously, the formation of associates was detected in poly(N-vinylimidazole) composites with copper nanoparticles [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the detected effect can be attributed not only to the influence of silver ions/nanoparticles on the polymerization conditions, but also to the intermolecular crosslinking of individual PVT macromolecules by nanoparticles into aggregates. Previously, the formation of associates was detected in poly(N-vinylimidazole) composites with copper nanoparticles [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since poly(1-vinyl-1,2,4-triazole) is in a partially protonated state in water, intermolecular interactions involving protonated and nonprotonated triazole rings can be expected, similar to the behavior of poly( N -vinylimidazole). 35,36…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the preparation of environmentally friendly, low-temperature-sintering metallic nanoparticles has become a research trend [ 21 , 22 , 23 , 24 ]. In past research [ 18 , 25 , 26 ], reports clearly demonstrated that ascorbic acid is a popular reducing agent. It is a natural and mild reducing agent with antioxidant properties and is widely used as a food preservative.…”
Section: Introductionmentioning
confidence: 99%